Outcomes and prognostic factors of Malaria-associated acute renal failure requiring haemodialysis at Chris Hani Baragwanath Academic Hospital - Moja, Lebogang (My University, 2018)
Background Plasmodium falciparum malaria is common in Sub-Saharan Africa. Acute kidney injury (AKI) is a complication of this infection. There are currently no studies that have been done in South Africa examining the outcomes in patients with AKI secondary to malaria infection who received acute haemodialysis. Objectives To describe the outcomes of malaria-associated AKI in patients treated with haemodialysis at Chris Hani Baragwanath Academic Hospital. Methods Clinical data from patients with confirmed P. falciparum malaria and AKI was analyzed to assess the demographics, initial clinical presentations, survival and predictors of mortality resulting in death. All patients presented to the Dumisani Mzamane Institute of Kidney Disease at Chris Hani Baragwanath Academic hospital from 01/01/2005 to 31/12/2014. v Results Our study showed that 77 (56 male, 21 female) cases of AKI were secondary to malaria. The majority (98.7%) were black, with a median age of 37 years (IQR: 19-69). Fever (93.5%), nausea and vomiting (92.2%), metabolic acidosis (74.7%) and anuria (58.4%) were the commonest clinical presentations. The overall mortality rate was 30%, with anuria and shock being the main predictors of mortality. Approximately 47/54 (87%) of patients who survived had improvement of the renal function with a serum creatinine dropping to less than 265micromol/l. Conclusion The initiation of haemodialysis combined with effective antimalarial therapy for the treatment of AKI in patients with P. falciparum malaria results in the improvement of renal function in majority of patients in this study.
A research report submitted to the University of the Witwatersrand, Johannesburg in fulfillment for the requirements of the degree of Master of Medicine 2017.
Keywords: Acute Kidney Injury; Malaria; Renal Dialysis (Haemodialysis)